Association of Household Food Security Status and Dietary Diversity among Children during COVID-19 - Ismail, Nashrah Adilah; Ab Rahim, Nur Shahida; Abdul Hamid, Syahrul Bariah (Jurnal Gizi dan Pangan, 2025)
The aim of this study is to identify food security status and its association with dietary diversity among children from low-income households (B40) during COVID-19. A cross-sectional study was conducted among 174 mothers and their children (<2 years old) residing in Selangor urban area. The data collection was collected through sociodemographic questionnaire to assess maternal and children’s sociodemographic characteristics, Household Food Insecurity Scale (HFIAS) to assess household food insecurity status, and Minimum Dietary Diversity (MDD)-Children 6‒23 months to assess dietary diversity score for children. The data was analyzed descriptively and a Chi-square test was used to find the relationship between food insecurity and dietary diversity. Findings showed that 105 participants (62.6%) was food insecure, there was 52.9% had low dietary diversity. There was no association between food insecure and dietary variety among B40 mothers living in urban area in Selangor. However, this study found that maternal education level (p=0.006), years of education (p=0.014) and the number of household income recipient (p=0.018) are significantly associated with the food insecurity. This study has provided the prevalence of food insecurity among B40 living in urban area and it is suggested that further research involving diverse household income of participants and research areas should be done to provide better insights on food insecurity and dietary diversity among children in Malaysia.